Perception of the transformation leadership at elite Romanian handball players - Gatzel, R.; Ion, L.; Stepan, A.-R.; Brandeanu, A.; Burcea George, B.; Cosma, G.-A. (Science, Movement & Health, 2023)
Aim. The present study aimed to contribute to the identification of the perception of the transformational leadership depending on some specific variables and establish the relations between the personality factors and the perception of the transformational leadership, among handball players. The present study involved 82 persons aged between 18 and 43 years, M = 30.73, AS = 7.20, handball players in activity or retired. Methods. The personality was measured with 32 items from IPIP (International Personality Item Pool) and the Transformational Leadership was measured with the Transformational Leadership Questionnaire. Results. The data showed that the transformational leadership is perceived more positively by Romanian athletes in comparison with foreign athletes, but it is not perceived more positively by athletes with national performance in comparison with the ones without national performance, neither from the ones with international performances. Conclusions. However, athletes who are satisfied with the personal physical training in comparison with those unsatisfied and the personality factors are, to some extent, significant predictors of the perception of the transformational leadership.